Longitudinal analysis of pinnipeds in the northwest Atlantic provides insights on endemic circulation of phocine distemper virus. Issue 1962 (10th November 2021) - Puryear, Wendy; Sawatzki, Kaitlin; Bogomolni, Andrea; Hill, Nichola; Foss, Alexa; Stokholm, Iben; Olsen, Morten Tange; Nielsen, Ole; Waltzek, Thomas; Goldstein, Tracey; Subramaniam, Kuttichantran; Rodrigues, Thais Carneiro Santos; et al.
Abstract : Phocine distemper virus (PDV) is a morbillivirus that circulates within pinnipeds in the North Atlantic. PDV has caused two known unusual mortality events (UMEs) in western Europe (1988, 2002), and two UMEs in the northwest Atlantic (2006, 2018). Infrequent cross-species transmission and waning immunity are believed to contribute to periodic outbreaks with high mortality in western Europe. The viral ecology of PDV in the northwest Atlantic is less well defined and outbreaks have exhibited lower mortality than those in western Europe. This study sought to understand the molecular and ecological processes underlying PDV infection in eastern North America. We provide phylogenetic evidence that PDV was introduced into northwest Atlantic pinnipeds by a single lineage and is now endemic in local populations. Serological and viral screening of pinniped surveillance samples from 2006 onward suggest there is continued circulation of PDV outside of UMEs among multiple species with and without clinical signs. We report six full genome sequences and nine partial sequences derived from harbour and grey seals in the northwest Atlantic from 2011 through 2018, including a possible regional variant. Work presented here provides a framework towards greater understanding of how recovering populations and shifting species may impact disease transmission.